Backhaul carrying scheme of TD-LTE microcell base station - Xiaoxia QIN; Chen WANG; Di QIAO (Dianxin kexue)
The deployment scenario，coverage strategy and site assignment of TD-LTE microcell base station（MiBS） are different from macrocell base station（MaBS）. Using PTN backhaul network of traditional MaBS to carry TD-LTE MiBS will face three challenges：low network performance，poor security and low intelligence. How to build an efficient，safe and intelligent backhaul network solution for MiBS was investigated. Based on China Mobile’s current network，PON+CMNet，PTN+CMNet，PON+PTN，PTN end-to-end four kinds of small cell backhaul network solutions were proposed and furtherly tested and verified. The result shows that 4 solutions all satisfy the communication business requirements of MiBS. In particular，PON+CMNet solution is better than the others in terms of network security，intelligence and efficiency.